The trends of complementary alternative medicine use among cancer patients - Abdul Rahman Jazieh; Khadega A. Abuelgasim; Husam I. Ardah; Mohammad Alkaiyat; Omar B. Da'ar (BMC, 2021)
Abstract Background The use of complementary and alternative medicine (CAM) is common among cancer patients and it may reflect the individual and societal beliefs on cancer therapy. Our study aimed to evaluate the trends of CAM use among patients with cancer between 2006 and 2018. Methods We included 2 Cohorts of patients with cancer who were recruited for Cohort 1 between 2006 and 2008 and for Cohort 2 between 2016 and 2018. The study is a cross-sectional study obtaining demographic and clinical information and inquiring about the types of CAM used, the reasons to use them and the perceived benefits. We compared the changes in the patterns of CAM use and other variables between the two cohorts. Results A total of 1416 patients were included in the study, with 464 patients in Cohort 1 and 952 patients in Cohort 2. Patients in Cohort 2 used less CAM (78.9%) than Cohort 1 (96.8%). Cohort 1 was more likely to use CAM to treat cancer compared to Cohort 2 (84.4% vs. 73%, respectively, p < 0.0001,); while Cohort 2 used CAM for symptom management such as pain control and improving appetite among others. Disclosure of CAM use did not change significantly over time and remains low (31.6% in Cohort 1 and 35.7% for Cohort 2). However, physicians were more likely to express an opposing opinion against CAM use in Cohort 2 compared to Cohort 1 (48.7% vs. 19.1%, p < 0.001, respectively). Conclusion There is a significant change in CAM use among cancer patients over the decade, which reflects major societal and cultural changes in this population. Further studies and interventions are needed to improve the disclosure to physicians and to improve other aspects of care to these patients.